Konsep Universal Sebagai Karakteristik Perbankan Syariah dan Moneter Ekonomi Islam - Rudy Itmamul Wafa (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the universal concept as a characteristic of Islamic banking (Perbankan Syariah) and the monetary economy of Islam in Indonesia. The research is motivated by the growing presence and significance of Islamic banking institutions in Indonesia, particularly following the enactment of Law No. 7 of 1992 and its revision through Law No. 10 of 1998. This study employs a normative-juridical research method supported by qualitative analysis of primary and secondary legal materials. The findings reveal that Islamic banking in Indonesia operates on several fundamental characteristics: universal (berlaku untuk semua orang tanpa memandang agama dan kemampuan ekonomi), varied products, facilitative services, just (adil), beneficial (maslahah), and transparent. The universal characteristic is particularly significant, demonstrating that Islamic banking principles are not limited to Muslim customers but are applicable to all segments of society. The study concludes that the universal nature of Islamic banking, grounded in the principle of rahmatan lil 'alamin, provides a solid foundation for its continued development in Indonesia and globally.